2015
DOI: 10.17344/acsi.2014.1109
|View full text |Cite
|
Sign up to set email alerts
|

Biological removal of triphenylmethane dyes from aqueous solution by Lemna minor

Abstract: The aim of this study is to investigate and develop a phytoremediation method for the removal of two triphenylmethane dyes (crystal violet and malachite green) using an aquatic plant, Lemna minor. The effects of operational parameters, such as aquatic plant quantity, initial dye concentration, initial pH of the solutions and temperature of the medium were studied in order to determine the optimum phytoremediation conditions. The plant's photosynthetic pigments were determined quantitatively in order to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 32 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…These spectra present some shifted bands; the band at 3287 cm −1 shifted to 3303 and 3280 cm −1 after Pb(II) and Cu(II) adsorption representative of O–H bond vibrations, 2027 cm −1 alkynes triple bond vibration shifted to 2036 and 2017 cm −1 which maybe a consequence of O–H complexation with the cations, the band at 1644 cm −1 representative for N–H groups shifted to 1635 and 1629 cm −1 , suggesting a complexation with Pb(II) and Cu(II), respectively, the band at 1416 cm −1 (S=O) shifted to 1421 and 1407 cm −1 due to interaction between cation and some functional groups like O–H and N–H. Similar results were presented by Török et al who studied dyes removal from aqueous solution using L. minor .…”
Section: Resultsmentioning
confidence: 98%
“…These spectra present some shifted bands; the band at 3287 cm −1 shifted to 3303 and 3280 cm −1 after Pb(II) and Cu(II) adsorption representative of O–H bond vibrations, 2027 cm −1 alkynes triple bond vibration shifted to 2036 and 2017 cm −1 which maybe a consequence of O–H complexation with the cations, the band at 1644 cm −1 representative for N–H groups shifted to 1635 and 1629 cm −1 , suggesting a complexation with Pb(II) and Cu(II), respectively, the band at 1416 cm −1 (S=O) shifted to 1421 and 1407 cm −1 due to interaction between cation and some functional groups like O–H and N–H. Similar results were presented by Török et al who studied dyes removal from aqueous solution using L. minor .…”
Section: Resultsmentioning
confidence: 98%
“…After purchase, the plants underwent a seven-day acclimatisation period in Hoagland solution to provide all the necessary nutrients [21]. Following this, plants of uniform length and weight (these morphological characteristics were recorded) of both species were put in 1 L of solutions with different dye concentrations (50-500 mg/L).…”
Section: Phytoremediation Studiesmentioning
confidence: 99%
“…The removal of these dyes and their metabolites from fish products has received little consideration in the literature. Previous studies focused on the removal of CV and MG from aqueous solutions using biosorbents (Raval, Shah, & Shah, ), ionic liquids (Lv, Cui, Zou, & Zheng, ), or biological removal (Török et al., ). Other studies showed that CV is able to bind to proteins such as bovine serum albumin (BSA; Qin, Yin, & Shen, ; Xu et al., ) and casein (Santhanalakshmi & Balaji, ).…”
Section: Introductionmentioning
confidence: 99%